Blockchain enabled Security Framework for handling Security and privacy challenges in Smart cities - et. al., Divya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the intriguing secure applications with regards to the keen city is communicating data to authentic clients, alluringly with client protection. Broadcast encryption has been considered as a helpful device to ensure the information security and give information access control. Most works in broadcast encryption are about the information security, while less consideration is paid to the information access control and the character protection. In this paper, in view of transmission encryption, we present a plan called Fully Privacy-Preserving and Revocable Identity-Based Broadcast Encryption, which protects the information security and the personality security of the collector just as the denied client. The information can be safely ensured and just the approved client can get to the information. The repudiation cycle doesn't uncover any data about the information substance and the collector personality. The general population adapts nothing about the recipient character and the repudiated client personality. These properties lead to pleasant applications in the shrewd city where character protection is attractive. The security of our plan is end up being semantically secure in the arbitrary prophet model